PACA (Predicting And Confirming Activity) Reading Strategies to Promote Students’ Teaching Strategy in TEFL 1 Class - Ririn Ambarini; Listyaning Sumardiyani; Subur Laksmono Wardoyo (Soegijapranata Catholic University, 2018)
This research is based on the study which is attempted to examine the use of PACA reading strategies to promote students’ teaching strategies in TEFL 1 class. The objectives of this study are (1) To find out the students’ teaching strategies in TEFL I class before using PACA reading strategies, (2) To find out the significant difference between the students who use PACA reading strategies and those who do not use PACA reading strategies in their capability of teaching strategies in TEFL I class. The population of this study is the fifth semester students of English Department in PGRI University of Semarang. There are six classes of TEFL I class in English Department and two classes are taken as the sample of the study. The classes are 5G and 5H. They are divided into the experimental class (5G) and the control group (5H). The result of the study shows that the students in the experimental class which were taught by using the technique of PACA Reading strategies to promote their teaching strategies had better achievement than the students in the control group which were taught without using the technique of PACA reading strategies. The average score of the pre-test of the experimental class was 76.72 and the control class was 72.85. The average score of the experimental class was 81.98 and the control class was 72.85. The pre-test and the post-test score then were calculated to get the t-test to know whether there was significant difference between the experimental class and the control class. The t-test was 0.47 and the t-table was 0.213. Then the t-test and t-table were compared. The data shows that the t-test was higher than the t-table. It means that there was significant difference between the experimental class and the control class.